2017
DOI: 10.3897/zookeys.671.12447
|View full text |Cite
|
Sign up to set email alerts
|

Aedes nigrinus (Eckstein, 1918) (Diptera, Culicidae), a new country record for England, contrasted with Aedes sticticus (Meigen, 1838)

Abstract: We report the discovery of Aedes nigrinus (Eckstein, 1918) in the New Forest of southern England, bringing to 36 the number of mosquito species recorded in Britain. Because it seems that this species has been misidentified previously in Britain as the morphologically similar Aedes sticticus (Meigen, 1838), the two species are contrasted and distinguished based on distinctive differences exhibited in the adult and larval stages. The pupa of Ae. nigrinus is unknown, but the pupa of Ae. sticticus is distinguished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…We followed the classification of Wilkerson et al (2015) for taxa in Aedini. The subgeneric placement for all species can be found in Harbach (2017) and Harbach et al (2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We followed the classification of Wilkerson et al (2015) for taxa in Aedini. The subgeneric placement for all species can be found in Harbach (2017) and Harbach et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, these findings demonstrated that the UK is at risk of introduction by invasive species of Aedes (Dallimore et al, 2017). In addition, Harbach et al (2017) discovered Ae.nigrinus (Eckstein, 1918) in the New Forest, southern England, which brings the total count of named species to 37 [35 native species plus two records of invasive species]. In addition, the occurrence of certain species has been very sporadic as in the case of Ae.vexans (Meigen, 1830); however, Medlock et al (2017b) reported a resident population of this species at Marston Marshes, Norwich.…”
Section: Introductionmentioning
confidence: 99%
“…There have been 36 mosquito species reported in the UK [ 16 ] of which 15 are Aedinae and 4 Culex . Based on records of abundance and feeding preference the following have potential as RVFV vectors: Ae.…”
Section: Introductionmentioning
confidence: 99%
“…DNA was isolated from individual eggs homogenized by electronic pestle, extracted using the DNeasy® Blood and Tissue Kit (Qiagen GmbH, Hilden, Germany) according to the manufacturer's instructions and amplified by polymerase chain reaction following the methods described in Harbach et al . (). Sequencing was carried out using an AB3500 genetic analyser (Applied Biosystems, Inc., Foster City, CA, U.S.A.).…”
Section: Methodsmentioning
confidence: 97%